Use of the tubular external fixator in the treatment of distal radial and ulnar fractures in small dogs and cats - Haas, B.; Reichler, I. M.; Montavon, P. M. (Veterinary and Comparative Orthopaedics and Traumatology, 2003)
Twenty-two fractures of the distal radius and ulna in small dogs and cats treated with a tubular external fixator system were evaluated. Radius/ulna fractures in toy breeds often occur in the distal metaphyseal region. Placing two screws through a bone plate in the distal radius in such cases is difficult even if a miniplate is used. The tubular external fixator allows multiple-pin clamping in parallel with a single connecting bar. Using this technique, four pins can be placed in a bone fragment, the length of which would hold only two screws in a 2.0 mini-DCP. The tubular external fixator was found to be a satisfactory alternative to bone plating for the fixation of distal radial/ulnar fractures, providing sufficient fracture stability with minimal soft tissue trauma.
Keywords: Tubular external fixator; radius/ulna fracture; small dog; cat